Impact of Hemodynamic Parameters on a Stenotic Aortic Valve: An in Vitro Study - Ebrahimi Dehshali, Massoud (My University, 2022)
Aortic Stenosis (AS) is a common valve disease, defined as the narrowing of the aortic valve. AS usually occurs together with other vascular and ventricular diseases; leads to insufficient blood supply to the body and adds stress on the heart. This study aims to investigate the impact of hemodynamic parameters on a stenotic aortic valve. Experiments were carried out in a cardiovascular simulator to replicate different physiological conditions. One aortic valve geometry was developed using computed tomography images, with four hypotheticals thicknesses: 0.3, 0.6, 0.8, and 1.0 mm. A physiological (non patient -specific) left ventricle volume waveform was applied as the input, and the valves were tested in different physiological conditions to investigate the impact of different parameters on the aortic stenosis. The effect of artery constriction on AS was evaluated by measuring pressure and flow rate and calculating Effective Orifice Area (EOA) and left ventricle (LV) workload. It was observed that a 49% increase in the Systemic Vascular Resistance (SVR) brings about a 27% reduction in EOA and a 79% increase in left ventricle workload. The coexistence of AS and left ventricle disorder in providing sufficient stroke volume reduces the valve opening area. Experimental results show a 30.5% (0.36–0.25 cm2) reduction in EOA when the stroke volume decreases by 50% (60-30 ml). A thicker valve with a higher resistance in turn decreased the EOA and increased the left ventricle workload. The results depict that the LV workload considerably increased with the leaflet thickness (34%). EOA, on the other hand, significantly decreased with the thickness (46.3%). This study highlights that hemodynamic parameters may exacerbate the aortic valve function in patients with AS. Moreover, to investigate the underlying logics of AS, other coexisting disorders need to be considered.